Changes in the Expression of Some Genes With Metabolic, VLDL and Antioxidative Effects After the Addition of Essential Oil Mixture to Drinking Water in the Liver of Domestic Geese (Anser anser Domesticus) - Özlem Durna; Mustafa Hitit; Zafer Usta; Gültekin Yildiz (Veterinary Medicine and Science)
ABSTRACT Studies have shown that essential oils not only increase cell viability but also affect lipid metabolism in mammals. However, the extent to which these effects are realized in goose liver has not yet been fully elucidated. The object of research is to investigate the effects of four essential oil mixtures (juniper oil, mint oil, thyme oil, rosemary oil) on lipid metabolic gene expressions in goose. We measured mRNA levels of metabolic genes (ACSBG2, ELOVL1, ELOVL2, CYP2Cl9, CYP2K1), antioxidative gene (SOD1) and very low‐density lipoprotein triglyceride (VLDL) synthesis genes (APOB, FOXO1, MTTP), in goose (Anser anser) liver. Search groups were formed as C (control; no additives), EK1 (0.4 mL/L essential oil mixture supplemented) and EK2 (0.8 mL/L essential oil mixture supplemented). The relative expression levels of genes in the liver were measured using RT‐qPCR. β‐Actin was used as reference gene control for normalization of qPCR data. As a result, essential oil supplementation downregulated metabolic genes compared to the control group. APOB gene among VLDL genes was significantly downregulated. Antioxidative effect gene was downregulated in parallel with the others. This indicates that essential oil intake with drinking water downregulates the genes involved in lipid metabolism in goose liver. Our data show that essential oils have a significant effect on the regulation of genes and pathways involved in hepatic lipid metabolism.